A cross-sectional study comparing live and recorded videos for undergraduate teaching of orthodontic appliance construction during the COVID-19 pandemic - Jonathan Yuen Jun Xian; Murshida Marizan Nor; Asma Alhusna Abang Abdullah; Asma Ashari; Noor Sam Ahmad (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2026)
Tier 2- Indexed by SCOPUS/MyCite